2015
DOI: 10.1039/c5ra13332g
|View full text |Cite
|
Sign up to set email alerts
|

Biohybrid hematopoietic niche for expansion of hematopoietic stem/progenitor cells by using geometrically controlled fibrous layers

Abstract: Biohybrid hematopoietic niche for expansion of hematopoietic stem/progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This 3‐D biohybrid scaffold facilitated high‐density expansion of multipotent HSPC. The microscale architecture of the electrospun fiber scaffolds, more closely resembling natural ECM, together with its mechanical properties and ability to enhance expression of Jagged‐1in co‐cultured MSC (known to play a role in the self‐renewal of HSPC through Notch‐1 – in HSPC – and Jagged‐1 – in stromal cells – interactions), were suggested to be relevant features of the 3‐D system in comparison to TCPS‐cultured HSPC and MSC . Electrospun poly(lactic acid) (PLLA) nanofibrous scaffolds, seeded with niche‐like units extracted from mice BM, were also shown to be suitable for implantation in irradiated mice and to contribute to the restoration of their hematopoietic system .…”
Section: ‐D Co‐culture Of Hspc and Mscmentioning
confidence: 99%
“…This 3‐D biohybrid scaffold facilitated high‐density expansion of multipotent HSPC. The microscale architecture of the electrospun fiber scaffolds, more closely resembling natural ECM, together with its mechanical properties and ability to enhance expression of Jagged‐1in co‐cultured MSC (known to play a role in the self‐renewal of HSPC through Notch‐1 – in HSPC – and Jagged‐1 – in stromal cells – interactions), were suggested to be relevant features of the 3‐D system in comparison to TCPS‐cultured HSPC and MSC . Electrospun poly(lactic acid) (PLLA) nanofibrous scaffolds, seeded with niche‐like units extracted from mice BM, were also shown to be suitable for implantation in irradiated mice and to contribute to the restoration of their hematopoietic system .…”
Section: ‐D Co‐culture Of Hspc and Mscmentioning
confidence: 99%
“…Previous studies have confirmed that 3D scaffolds could support the better maintenance of HSCs. However, if use MSCs or ECM protein as feeder layer, their consequences could be improved, because of cellcell interaction between CD34+ cells and feeder cells or ECM [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is relatively easy to obtain HSPCs from umbilical cord blood (UCB); such cells proliferate better than BM-and PB-derived cells. As might be expected, the number of cells available from a single umbilical cord is limited [4][5][6][7]. Ex vivo expansion of HSPCs is thus essential.…”
Section: Introductionmentioning
confidence: 99%
“…However, cross-contamination is possible and long-term engraftment is poor. Thus, many researchers have constructed three-dimensional (3D) environments mimicking the in vivo niches of HSPCs [10][11][12] in an effort to enhance cell attachment to structural supports and enable cell-cell and cell-matrix interactions, thus improving cellular potential [6,13,14]. Therefore, when functional ex vivo expansion of HSPCs is essential, the 3 D culture conditions should first be considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation